EFEKTIVITAS TUMPUAN ISOLATOR KARET UNTUK MENGURANGI AKSELERASI SEMU GEMPA BUMI - Budiadi, Andri (Jurnal Teknik Sipil, 2026)
This research paper is to study the effect of using Rubber Bearing as Base Isolator. Two analyses are performed in this study. The first analysis is using a whole building structure to be calculated its period and to be estimated its pseudo acceleration for both fixed and isolated bases. The second analysis, period calculation and estimation of pseudo acceleration is using a single column of the building structure. Method of analysis is using basic vibration formulas. The calculated parameters are stiffness of the structure, damped frequency, undamped natural frequency and period of vibration.  Using response spectra of the building, pseudo acceleration is estimated by plotting vibration period for both fixed and isolated supports. Trial-and-Error processes are needed to find where along response spectra three lines types two pairs of the coordinate of period and pseudo acceleration reveal the increasing value of period and decreasing value of acceleration.   Comparing the pseudo acceleration of fixed and isolated base, for the first analysis, the pseudo acceleration decreases up to 53,85 %. Pseudo acceleration decreases by 51,79 % for the second analysis. The decreasing value of earthquake acceleration is only possible when both fixed and isolated base structural periods fall in the Curved down line in the response spectrum diagram.